THE INFLUENCE OF MOTIVATION FACTOR AND HYGIENE FACTOR ON EMPLOYEE PERFORMANCE WITH ISLAMIC WORK ETHICS AS A MODERATING VARIABLE (STUDY OF ASN & NON-ASN EMPLOYEES IN DISPORAPAR BALANGAN REGENCY) - Muhdiansyah Muhdiansyah; Rini Rahmawati (INJOSEDU: International Journal of Social and Education, 2025)
Globally, the Indonesian Government issued Law number 5 years which basically demands that ASN be professional, have core values , and be of high quality. However, this is inversely proportional to the situation of das sein in the field. During preliminary research , researchers found that of the 31 ASN & 85 non-ASN who worked at the Balangan Regency Disporapar, not all of them had high work motivation. This research aims to find out whether employee performance is influenced by factors such as Motivation Factor, Hygiene Factor and Islamic Work Ethics . Apart from that, it also aims to find out whether Islamic Work Ethics moderates the relationship between Motivation Factor and Hygiene Factor on Employee Performance. This type of research uses surveys with a quantitative approach. Data was collected using 4 instruments, namely observation, interviews and documentation/literature study as well as questionnaires distributed to 54 ASN and non-ASN people in the Balangan Regency Disporapar. Samples were taken using purposive sampling technique . After the data is obtained, it is then processed and analyzed using SmartPLS version 4.0. The research results show that on the one hand, the motivation factor and hygiene factor variables have a positive and significant effect on employee performance. Meanwhile, on the other hand, it was found that the Islamic Work Ethics variable had no effect on employee performance. In this research, it was also found that Islamic Work Ethics was unable to moderate the relationship between motivation factors and employee performance. Likewise with the relationship between hygiene factors and employee performance, which is also unable to be moderated by the Islamic Work Ethics variable